Análise bibliométrica de teses sobre letramento disponíveis na Biblioteca Digital Brasileira de Teses e Dissertações (1997-2016) - Sousa, Raquel Juliana Prado Leite de (Universidade Federal de São Carlos, 2019)
In recent years, there has been increasing insertion of literacy in scientific production in the field of Education and also in the day to day of schools, with an expansion of the concept of the teaching of reading and writing for diverse disciplines. Faced with this expansion, we reached the research problem: how are the doctoral researches in Brazil on the subject of literacy in relation to its theoretical frame of reference and its authors? The general objective is to understand how the formation of the scientific field on literacy in Brazil and its research front by the identification of its theoretical frame of reference and its main authors cited in the theses of the Brazilian Digital Library of Theses and Dissertations (BDTD). As specific objectives, we intend to: raise a theoretical reference on literacy, in order to delineate its conceptual developments in Brazilian research; to elaborate bibliometric indicators on the scientific production in literacy through variables such as: a) authorship; b) keywords; c) areas of knowledge; d) research lines; e) research institutions; f) financing; g) gender of the researchers; h) typology of the mentioned sources; etc.; and to analyze the citations present in the theses of the BDTD, in order to identify the bibliographic support, the theoretical frame of reference and the research front. The hypotheses to be verified in this work are: most of the theses produced on the subject come from the Southeast region, like other areas of knowledge; in this way, the authors, teachers, educational institutions of affiliation of these theses, as well as their quotations, influence the national scientific production on literacy, impacting the formation of the theoretical conceptual framework on the subject, in the analysis of citations, in the promotion of research, etc. ., as in the transference of literate practices from the dominant culture to subcultures; and there are predominance of Brazilian authors on the research fronts, with less reference to foreign authors. The corpus consists of 237 theses present in the Brazilian Digital Library of Theses and Dissertations defended between 1997 and 2016. Three studies were carried out: Study 1: survey and analysis of the 237 theses selected for the research corpus, in order to generate a profile of the PhD work developed over two decades considering the following variables: a) temporal evolution; b) geographical and institutional distribution; c) guidance and gender; d) use of keywords; Study 2: profile of the references, in order to draw a profile of the documents cited in the theses deposited in the BDTD on the subject, considering the variables: a) document typology; b) type of authorship; and d) cited journals; and Study 3: productivity and research front, by the productivity measurement and the research front of the authors cited in the 237 theses. This work is based on the interdisciplinarity of theoretical references in the areas of Education, Linguistics and Information Science. There was an increase in doctoral research between 1997 and 2016, with peaks of defenses between 2007 and 2016. The data showed that there is an imbalance in the development of doctoral research on literacy in the country, with concentration of production in a few regions, institutions and confirmed one of the hypotheses of the research. It was noticed the predilection for the citation of books, with 11,620 references against 5,207 of chapters and 4,172 of articles. The calculation of the research front allowed to indicate the most cited authors. The application of the natural Logarithmic, a study carried out in a new way in this thesis, made it possible to observe the growth behavior of the citations and to verify the exact point of change between the less cited and the most cited groups, and could replace the traditional method of computation. It was observed the existence of outliers, that is, authors who stand out receiving more quotations than the other names of the research front. It was noted that the most cited authors, who make up the research front, are mostly from Linguistics and Education, respectively, supported by authors from areas such as Philosophy, Psychology, Sociology, Anthropology, Semiotics, History, Psychoanalysis, Communication and Information Science. The influence of the researchers of the currents of poststructuralism and of postmodernism. The hypothesis that there is predominance of Brazilian authors in the research fronts was confirmed only for documentary types chapters and articles; however, considering that the percentage of national authors of these documents represents a little more than half of the citations, there was balance of Brazilian and foreign authors. The methodologies used allowed to fully fulfill the proposed objectives, obtaining indicators that helped to understand the constitution of the scientific field on literacy in Brazil, in the identification of its research front and its theoretical frame of reference. It should be emphasized that, because it is an exploratory research and an unprecedented one, this work aims to provoke questions and to point out cuts that may need more attention, serving as a starting point scientifically based on future research.
Bibliometric analysis of theses on literacy of the Brazilian Digital Library of Theses and Dissertations (1997-2016)
Keywords: Educação; Letramento; Bibliometria; Cientometria; Análise de citação; Frente de pesquisa; Outliers de pesquisadores; Produção científica; Education; Literacy; Bibliometrics; Scientometrics; Citation analysis; Research front; Outliers of researchers; Scientific production; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM